L'expérience québécoise - Robic, Louise (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
Quebec is the only Canadian Province to have affirmed its rights in the area of immigration by creating in 1968 a Department of Immigration. The Department has as its fundamental mission to provide a framework of support and orientation for immigration in the Province. The expression "humanitarian immigration" applies to two categories of people : refugees, as defined by the Geneva Convention, and more imposing those persons who, without being refugees, are selected for immigration due to humanitarian reasons. In recent years Quebec has welcomed 12 000 to 20 000 persons who have come to Canada claiming refugee status. The people of Quebec have shown openness and generosity in insuring newcomers with financial support and diverse means of welcome ranging from health care and housing to legal aid. The Quebec experience inspires thought on the relativity of the generosity and the fundamental contradiction of humanitarian immigration. The solution to the problem posed by the existence in the world of twelve million refugees can not be found only through immigration, but rather for a major part, by the recognition and guarantee of the respect of Human Rights.